Effects of alfalfa particle size and starch content in diets on feeding behaviour, intake, rumen parameters, animal performance and meat quality of growing lambs. (March 2020) - Francisco, Alexandra E.; Janíček, Martin; Dentinho, Teresa; Portugal, Ana P.V.; Almeida, João M.; Alves, Susana P.; Fialho, Letícia; Jerónimo, Eliana; Bessa, Rui J.B.; Santos-Silva, José
Abstract: Thirty-two crossbred Merino branco male lambs were randomly allocated to eight diets, combining two forms of alfalfa presentation (chopped or ground), with four barley grain levels (0%, 11.2%, 21.3% and 33% dry matter (DM)), balanced by low starch agro-industrial by-products (LSBP). The diets were supplemented with 6% soybean oil and included 40% of alfalfa in DM. The lambs were individually housed and the trial lasted six weeks. Intake of DM, average daily weight gain (ADG) and carcass weight were higher with ground alfalfa ( P < 0.01). Replacing barley grain by LSBP reduced linearly DM intake and ADG ( P < 0.001) but increased meat tenderness ( P = 0.046). Regardless of the treatments, meat showed a healthy biohydrogenation fatty acid (FA) profile, with high proportions of t 11-18:1, c 9, t 11-18:2 and a t 10-18:1/ t 11-18:1 ratio clearly below 1. The reduction of barley in diet had a moderate positive impact on meat FA composition, decreasing t 10-18:1, which was enhanced by the increase of forage particle size. Highlights: Replacing barley grain with low-starch agro-industrial by-products decreased lamb growth rate. Reducing barley grain in lamb diets reduced t10–18:1 content in meat. Increasing of alfalfa particle size favored t11 biohydrogenation pathways.